P10 Light may be used to differentiate mesothelioma from benign pleural disease at the bedside. (15th November 2016) - Oswald, NK; Robertson, A; Rajesh, P; Steyn, R; Bishay, E; Kalkat, M; Naidu, B
Abstract : Introduction: Monitoring patients at risk of mesothelioma, earlier diagnosis and improving diagnostic tests are top research priorities set by the James Lind Alliance. Chest wall motion (CWM) can be quantified using structured light plethysmography (SLP). During SLP a single source of visible light projects a chequerboard grid onto the anterior chest wall of a patient; two spaced cameras record changes in the contours of the grid to calculate thoracic volume changes. This study aimed to assess whether there are quantifiable differences in CWM between benign pleural disease and mesothelioma using SLP. Methods: Patients attending the preoperative assessment clinic for an elective diagnostic pleural biopsy were prospective recruited. After giving consent, patients underwent a timed 5 minute SLP recording of tidal breathing whilst resting in an upright seated position. Recordings were done prior to surgery and analysis of the SLP recording was performed by a blinded technician. Histology results were collected after surgery and Mann Whitney U two tailed tests of SLP values performed. Results: Fifteen patients were recruited with a median age 71 (23–93 range), 90% were male. Patients subsequently diagnosed with mesothelioma (n = 4) had significantly different values in three measurements: the inspiratory to expiratory time ratio (Ti/Te, p = 0.009), breath phase between ribcage and abdomen (breath phase RC2AB, p = 0.013) and the variation in ratio of inspiratory flow at 50% of tidal motion to expiratory flow at 50% of tidal motion (IE50 IQR, p = 0.004). Median and interquartile ranges for breath phase (a measure of CWM synchrony) are shown in Figure 1 . The recording process was highly acceptable to patients. Conclusions: Mesothelioma affects the ratio of time for inspiration and expiration as well as synchrony in CWM and variability of the breathing pattern. SLP is rapid, portable, non-invasive, requires minimal operator training and involves no radiation. The differences found indicate that CWM measurement is a promising tool to diagnose or exclude mesothelioma and potentially to monitor patients at risk of mesothelioma, further studies using SLP in this context are indicated.